Research on CSI feedback and precoding in FDD cell-free massive MIMO systems - ZHANG Dekun; BAI Baoming (Dianxin kexue)
For frequency division duplexing (FDD) cell-free massive multiple input multiple output (MIMO) systems, maximizing downlink capacity relies on designing a precoding matrix that achieves high beamforming gain and effectively suppresses multi-user interference. The accurate acquisition of downlink channel state information (CSI) is essential for calculating precoding matrix. However, due to the imperfect reciprocity between uplink and downlink in FDD systems, securing low-overhead and high-precision downlink CSI remains an industry challenge. Therefore, a CSI measurement and feedback scheme on the basis of co-located spatial user clusters was proposed, along with a two-stage precoding optimization scheme that integrated cluster-level CSI feedback. Firstly, equivalent downlink spatial correlation was obtained based on the calculation of uplink and downlink statistical reciprocity, and co-located space user clusters were jointly constructed using the downlink channel quality and equivalent spatial correlation. Secondly, a dynamic CSI coherent measurement scheme was designed based on large-scale fading characteristics and CSI pilot port capacity constraints, and a statistical CSI feedback scheme for co-located space clusters was developed, significantly reducing feedback overhead. Finally, during the CSI measurement phase, large-scale slowly varying interference elimination precoding was designed using the statistical covariance matrix between cluster users. During the downlink scheduling phase, real-time multi-user interference elimination precoding within clusters was designed on the basis of the signal-to-leakage-and-noise ratio (SLNR) algorithm. The two were cascaded to form the optimized downlink precoding weight values for each user. Simulation results show that the proposed CSI feedback optimization scheme reduces the feedback overhead by 34% compared with the path gain information feedback strategy in the literature, and the two-stage precoding optimization scheme improves the FDD non-cellular massive MIMO spectral efficiency by 10.8% compared with the SLNR precoding.